Willingness to accept energy-saving measures and adoption barriers in the residential sector: An empirical analysis in Beijing, China. (November 2018) - Jia, Jun-Jun; Xu, Jin-Hua; Fan, Ying; Ji, Qiang
Abstract: This paper investigates the public attitude toward and willingness to accept six energy-saving measures in the residential sector in Beijing, China. The qualitative results derived from questionnaires show that financial incentives and the desire to reduce energy consumption are the most significant factors driving the public to adopt the measures and that the unavailability of electric vehicle (EV) chargers is a crucial barrier to the promotion of EVs. The quantitative results indicate that socioeconomic variables have a greater impact on technical energy-saving measures than behavioral ones. Renters or individuals with a high risk preference have a lower willingness to accept energy-efficient air conditioners. The price of gasoline, convenience of EV chargers, EV policy package, and environmental concern can significantly influence willingness to purchase an EV. With regard to behavioral energy-saving measures, control of the heating system and the influence of nearby people (spillover effect) significantly increase the preference for closing windows when the heating is on. The public transportation convenience, high gasoline prices and the congestion charge have significant effects on residents' willingness to use public transportation. Infrastructure upgrades to heating and transportation would remove adoption barriers and facilitate energy conservation. Price policies and preferential policies related to EVs could have a significant impact on household choice of transportation mode. Finally, increasing the public energy-saving awareness and environmental concern is recommended to facilitate the promotion of energy-saving options. Highlights: Residents' willingness to accept six energy-saving measures are investigated. Reasons and barriers of the adoption of energy-saving measures are identified. Socioeconomic variables have a more impact on technical energy-saving measures. Infrastructure upgrades to heating and transportation facilitate energy saving. Price policies for appliances and preferential policies favoring EVs are effective.